Using ad hoc wireless networks to enable intelligent transport systems: the design and analysis of the TH(O)RP routing protocol - Morrison, Daniel Weich (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.